Gender Determination by Cone-Beam Computed Tomography Analysis of Mental Foramen in North Indian Population - Balwinder Singh; Alisha Madan; Kirandeep Kaur; Prabhnoor Kaur Saraya; Deepti Bhatnagar; Amit Aggarwal (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Gender determination is crucial in forensic odontology, particularly during mass disasters where unknown craniofacial fragments are the only source of information. Aim: To determine sexual dimorphism by cone-beam computed tomography (CBCT; 3D) analysis of mental foramen among the North Indian population. Materials and Methods: One hundred and twenty CBCT scans were analyzed to assess the position of the mental foramen. The distance from the superior border of the mental foramen to the lower border of the mandible (SLM) and the distance from the lower border of the mental foramen to the lower border of the mandible (ILM), along with the thickness of the lower border of the mandible, were recorded, tabulated, and subjected to statistical analysis. Results: The mean distance of the right SLM among male and female subjects was 16.03 ± 1.91 mm and 15.35 ± 1.39 mm, respectively. The measurements for the left SLM were 15.83 ± 1.66 mm in males and 14.49 ± 1.70 mm in females. Similarly, for the right ILM, the mean distance was measured as 13.04 ± 1.86 mm in males and 12.05 ± 1.20 mm in females, and for the left ILM, the mean distance was 12.74 ± 1.46 mm in males and 11.87 ± 1.53 mm in females. There was a statistically significant difference between the genders and the sides of SLM and ILM. Conclusion: The distances from the mental foramen to the lower border of the mandible exhibit sexual dimorphism and can be used to predict gender in the North Indian population.